Strategi Jihad Digital Sebagai Upaya Perlawanan Informasi Negatif: Studi Metode Istihsan pada Akun Instagram - Rasyid, Arbanur; Asmara, Musda; Lubis, Maulana Arafat (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This research aims to provide educational insight for netizens on how to get smart ways to counteract negative information on social media, especially Instagram as the object of this discussion. The method used by the author in this discussion is a literature study with the main sources being documentation, news, articles that are in accordance with the topic of study. The results of this study are that there are several groups of netizens who are easily influenced by negative news, they are also easily provoked based on social media behavior. Digital jihad strategies on Instagram accounts using the istihsan method as a step to combat misinformation or news; negative by verifying or "tabayyun", then filtering the news sources and measuring in terms of benefits and harm, so that valid conclusions can be found regarding the source of the news circulating on social media Instagram.